COMPUTERIZED SYSTEM FOR FILING INCOMING AND OUTING MAIL AT THE GENERAL CENTER OF THE PEMLI JUANA RIVER REGION - Diah Yulianti Nuraisyah; Migunani Migunani (Journal of Engineering, Electrical and Informatics, 2021)
This study aims to develop an Information System for Archiving Incoming and Outgoing Letters at the Balai Besar Pemali Juana River Basin. the accuracy and security of archived documents can be guaranteed. So that when an archiving information system is needed. In addition, with this system the admin or archiving officer can also send disposition messages via SMS messages in the system, so that disposition messages will be conveyed more quickly to the relevant staff. The final result of the design resulted in an Information System Application for Archiving Incoming and Outgoing Letters at the Pemali Juana River Basin Center to make it easier for admins to search for incoming mail or outgoing mail control card data when needed. This Incoming and Outgoing Mail Archiving Information System discusses computerized mail archiving, if it is an incoming letter then it is recorded on the incoming mail control card and if it is outgoing mail it is recorded on the outgoing mail control card carried out by the admin and stored in the database.